Okiskinwahamâkew: Reflecting on teaching, learning and assessment - Steinhauer, Patricia J. (Frontiers in Education, 2023)
This paper looks at assessment views held by Alberta Education in regards to teaching and learning for educators in Alberta. The standardization model of teaching and assessment excludes Indigenous thought systems articulated through rigorous thought processes in the nehiyaw mâmitoneyihcikan – the Cree mind and intelligences. Infusion, integration, indigenization models that privilege the dominant educational design continue to perpetuate an invisible colliding space that impacts the Indigenous thinker and learner. Privileging Indigenous language thought systems that are rich in multidimensional processes are presented to address current notions of teaching and assessment. Looking through the lens of the Indigenous language system and addressing the politics of literacy uncovers nehiyaw mâmitoneyihcikan – the Cree mind. This rich thought system reveals a sophisticated system that operates omni and multidimensionally from and within a compassionate mind – a value based way of seeing and engaging. Honouring nehiyaw thought systems, processes of coming to know and respecting Indigenous understandings of teaching and learning, lead to considering the rigorous nehiyaw understanding of okiskinwahamâkew - Indigenous informed teaching guide.